Defining the paralympic athlete: normative values for scat major components in healthy paralympic athletes. Issue 11 (25th May 2017) - J Moreau, William; Walden, Taylor; Nabhan, Dustin
Abstract : Objective: Describe normative baseline SCAT 2 and 3 (SCAT) performance in elite Paralympic athletes. Design: Retrospective cohort. Setting: United States Olympic Committee Sports Medicine Clinics. Participants: Sixty-nine SCAT baseline evaluations were performed on a population of 60 elite athletes Paralympic (17 women and 43 men, mean age 30.1±7.3 years) representing 5 Summer and Winter Olympic sports as part of multimodal concussion programing. Intervention: No intervention was applied. The SCAT evaluations were administered as a component of a baseline testing on healthy athletes. Main outcome measurements: Baseline SCAT performance on major components is described. T-tests were used to compare differences in baseline performance by sex. Results: During baseline evaluations, elite Paralympic athletes reported a mean (95%CI) of 2.2 (1.1–3.3) symptoms with an average symptom severity score of 4.7 (2.8–6.6). Mean scores on SCAT components in this population were; orientation 4.9 (4.8–5.0), immediate memory 14.3 (13.9–14.8), concentration 4.0 (3.7–4.2), tandem gait 15.4 (12.3–18.6), delayed recall 3.7 (3.4–4.0), balance 4.4 (1.9–7.06), SAC total 26.6 (25.8–27.4). This group reported a history of 2.6 (1.4–3.8) previous concussions. There were no significant differences between males and females in components of the SCAT. Conclusions: Population specific normative values for baseline SCAT performance in a population of elite Paralympic athletes are presented in this cohort study. Clinical relevance: Paralympic athletes are an understudied population. Clinicians are encouraged to reference population specific normative values when interpreting SCAT performance. For athletes with impairments, individual baselines may be preferred to the wide distribution of functional capacity. Acknowledgements: None. Competing interests: None.